2015
DOI: 10.1109/ted.2015.2444911
|View full text |Cite
|
Sign up to set email alerts
|

Interface State Artefact in Long Gate-Length AlGaN/GaN HEMTs

Abstract: Dispersion in capacitance and conductance measurements in AlGaN/GaN high-electron mobility transistors is typically interpreted as resulting from interface states. Measurements on varying gate-length devices and a model of an interface-trap-free device are used to demonstrate that the distributed-resistance-induced dispersion is significant for 1-MHz measurements if the gate length exceeds ∼10 µm. Hence, interface state density measurements using the conductance technique need to use shorter gate-length device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The real component of the admittance is the conductance, which when plotted as G ω against ω displays a characteristic peak for each V disc tested [11], as shown in Figure 2. The fitting algorithm used the logarithm of the ratio of the peak positions for the measured and model curves as the optimisation target to be minimised.…”
Section: Methodsmentioning
confidence: 99%
“…The real component of the admittance is the conductance, which when plotted as G ω against ω displays a characteristic peak for each V disc tested [11], as shown in Figure 2. The fitting algorithm used the logarithm of the ratio of the peak positions for the measured and model curves as the optimisation target to be minimised.…”
Section: Methodsmentioning
confidence: 99%
“…They reported an interface state density of 1 Â 10 12 cm À2 with an energy of 0.3 eV below the conduction band. Recently, Waller et al 30 showed that using the conductance method for extracting interface states is valid only for HEMTs with short gate length (L G < 10 lm). Utilizing this method for HEMTs with long gate lengths results in exaggerated interface state density.…”
Section: Charge States At the Algan-gan Interfacementioning
confidence: 99%
“…Utilizing this method for HEMTs with long gate lengths results in exaggerated interface state density. Waller et al 30 measured an interface state density of 5 Â 10 10 cm À2 in the Ga-polar GaN/AlGaN HEMTs which had gate lengths lower than 10 lm. The reason behind the formation of these interface states is not well-understood yet.…”
Section: Charge States At the Algan-gan Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…21,[25][26][27] The method reported by Yang et al 27 f -dispersions of the second slope onset (V ON ) in the ac-CV characteristics (Fig. 2), the interface-state density of LPCVD-SiN x /GaN-cap/AlGaN was calculated by…”
mentioning
confidence: 99%